Blurring Boundaries and Work-Life Integration: A Theoretical and Empirical Review of Their Effects on Productivity, Life Satisfaction, and Organizational Commitment: Blurring Boundaries and Work-Life Integration: A Theoretical and Empirical Review - Asa Sheila Amelia; Fauzi Ichwani (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Blurring boundaries between work and personal life have become a defining feature of contemporary work systems, intensifying through digital connectivity, flexible working arrangements, and the expansion of remote and hybrid work structures. This review synthesizes theoretical perspectives and empirical evidence to examine how blurring boundaries conceptualized as work-life integration shape employee productivity, life satisfaction, and organizational commitment. Drawing on boundary theory, role integration frameworks, and modern research on digital labor, the findings demonstrate that work-life integration can enhance productivity by increasing autonomy, flexibility, and reducing transition costs. However, boundary permeability may also induce technostress, work intrusion and role overload, undermining wellbeing and performance. Life satifaction improves when integration is voluntary and aligned with personal preferences but decreases when constant connectivity disrupts recovery time or intensifies conflict between roles. Organizational commitment strengthens when integration practices are perceived as supportive and empowering but weakens when blurring boundaries are associated with surveillance or exploitation. This review clarifies conceptual ambiguities, identifies moderating conditions underlying positive and negative effect, and provides directions for future research on adaptive boundary management in digital driven work environments.